2017
DOI: 10.1007/s13280-017-0971-1
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the yield response to phosphorus fertilization based on meta-analyses of long-term field experiments

Abstract: Phosphorus (P) fertilizer recommendations in most European countries are based on plant-available soil P contents and long-term field experiments. Site-specific conditions are often neglected, resulting in excessive P fertilizer applications. P fertilization experiments including relevant site and soil parameters were evaluated in order to analyze the yield response. The database comprises about 2000 datasets from 30 field experiments from Germany and Austria. Statistical evaluations using a classification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…Even the high P application rate of 44 kg P ha −1  year −1 could not provide enough plant-available P for optimal growth and P uptake at low pH. The interaction between the soil pH and plant P availability is in agreement with other findings, where meta-studies demonstrated that a low soil pH was a crucial factor for yield response to P application, specifically at low soil P levels (Kuchenbuch and Buczko 2011; Buczko et al 2017). This clearly demonstrated that a too low soil pH has to be adjusted by liming to increase the use efficiency of fertilizer P. However, it can also be concluded that if the soil pH was increased to a soil type-specific optimal level, 3–4 mg CAL-soluble P 100 g soil −1 was sufficient to allow for adequate yields of all three tested crop species, when P fertilizer was applied annually.…”
Section: Discussionsupporting
confidence: 89%
“…Even the high P application rate of 44 kg P ha −1  year −1 could not provide enough plant-available P for optimal growth and P uptake at low pH. The interaction between the soil pH and plant P availability is in agreement with other findings, where meta-studies demonstrated that a low soil pH was a crucial factor for yield response to P application, specifically at low soil P levels (Kuchenbuch and Buczko 2011; Buczko et al 2017). This clearly demonstrated that a too low soil pH has to be adjusted by liming to increase the use efficiency of fertilizer P. However, it can also be concluded that if the soil pH was increased to a soil type-specific optimal level, 3–4 mg CAL-soluble P 100 g soil −1 was sufficient to allow for adequate yields of all three tested crop species, when P fertilizer was applied annually.…”
Section: Discussionsupporting
confidence: 89%
“…According to Figure 4, estimated primary productivity was high when plant-available phosphorus contents were between 46 and 135 mg kg −1 . Plant-available phosphorus contents are known to affect primary productivity (Sheil et al, 2016;Buczko et al, 2018;Trajanov et al, 2018). Furthermore, the classification tree confirms findings from Spiegel et al (2001), who reported that very high yielding crops grown on soils with low plant available phosphorus concentrations are more likely to result in lower yields.…”
Section: Primary Productivity Decision Support Modelsupporting
confidence: 85%
“…First, the analyses are not limited to only a few attributes or pair-wise comparisons for modeling a certain soil function, but all available data can be used. Using all the available data enables discovering interesting and new-often unexpected-patterns from the data (Buczko et al 2018). This can provide new knowledge and insights about the problem at hand (De'ath and Fabricius 2000; Debeljak and Džeroski 2011;Jiawei et al 2006;Veenadhari et al 2011).…”
Section: Applicability and Scalability Of The Resultsmentioning
confidence: 99%